Analyzes The Performance Of The Budget Expenditure in the Law Division of the Mataram City Regional Secretariat - Dewi Amri Anami (PT ARRUS Intelektual Indonesia, 2023)
This research analyzes the performance of the budget expenditure in the Law Division of the Mataram City Regional Secretariat. The aim is to determine how the performance of budget expenditure is viewed through variance analysis, expenditure growth analysis, expenditure compatibility analysis, and expenditure efficiency ratio analysis. This study employs a descriptive approach with quantitative data, while the data collection techniques used are observation, documentation, and interviews. The results of this study indicate that the performance of budget expenditure, as seen from the variance analysis of the expenditure during the period of 2017-2021, is considered good. The performance of budget expenditure, based on the expenditure growth analysis during the period of 2017-2021, tends to decrease, but it is not due to poor performance. Therefore, the performance of budget expenditure is still considered good. The expenditure performance, viewed from the expenditure compatibility analysis, is good for operational expenses, while capital expenditures were only carried out in 2018-2019. The performance of budget expenditure, as seen from the expenditure efficiency ratio analysis, is very good, as the budget realization does not exceed the budget, and since the result is less than 100%, the Law Division of the Mataram City Regional Secretariat has achieved budget efficiency.